(untitled) (Malaysian Journal of Civil Engineering, 2018)
Seismic hazard analysis, an approach to get an estimate of the strong ground-motions at any particular site, is mainly intended for earthquake resistant designs or for seismic safety assessments. The hazard analysis usually attempts to analyze two different kinds of anticipated ground motions, â€œThe Probabilistic Seismic Hazard Analysisâ€ (PSHA) and â€œThe Deterministic Seismic Hazard Analysisâ€ (DSHA). A sincere effort is made herein to perform seismic hazard analysis for Ambikapur District of Chattisgarh state using a Deterministic approach. The study broadly consists of two parts, the first part basically gives a detailed overview of the seismicity of the region and identification of various faults existing within the district with all their particulars and the second part includes DSHA analysis for the same. An effort was made to compile the occurrence of past and recent seismic activities within 300 km radius, around the District Headquarter Ambikapur. The main benchmark and indicator that needs to be involved in carrying out the hazard analysis which is the correctness and completeness of the data was attained to the utmost. The knowledge presented in this paper helps in evaluating the seismicity of the region around, District Headquarter Ambikapur after statistical analysis of the database. Finally the results are furnished in the form of peak ground acceleration (PGA) which can be used directly by engineers as fundamental considerations, for generating earthquake-resistant design of structures in and around District Headquarter Ambikapur.